2023
DOI: 10.3390/ani13142350
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Bacillus and Enterococcus faecium 669 Probiotic Strains When Added to Different Feed Matrices Used in Dairy Production

Bruno I. Cappellozza,
Audrey Segura,
Nina Milora
et al.

Abstract: Few data are available evaluating the stability of direct-fed microbials (DFM) following their inclusion in different feed matrices. Therefore, six Exp. evaluated the recovery of bacilli spores (BOVACILLUSTM; Exp. 1 to 3) and an Enterococcus faecium DFM (LACTIFERM®; Exp. 4 to 6) when included in different feed preparations. The Bacillus-based DFM was included into pelleted feed prepared in different temperatures (75 to 95 °C), whereas both DFM were assessed in premix and milk replacer preparations. Bacillus sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Several studies reported that galactomannan provide nutrients for beneficial microbes in the gastrointestinal microbiota ( 34 ) and D-mannitol can also become energy sources for bacteria growth in the rumen ( 35 ). Also, Cappellozza et al ( 36 ), reported that the inclusion of Bacillus- based probiotics can increase rumen in vitro gas production due to the production of various enzymes by Bacillus sp. The protease produced from Bacillus.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that galactomannan provide nutrients for beneficial microbes in the gastrointestinal microbiota ( 34 ) and D-mannitol can also become energy sources for bacteria growth in the rumen ( 35 ). Also, Cappellozza et al ( 36 ), reported that the inclusion of Bacillus- based probiotics can increase rumen in vitro gas production due to the production of various enzymes by Bacillus sp. The protease produced from Bacillus.…”
Section: Discussionmentioning
confidence: 99%